PEMBUATAN DIGITAL ELEVATION MODEL (DEM) DENGAN KETELITIAN PIXEL (10 METER X 10 METER) SECARA MANUAL DI SUB-DAS RAWATAMTU - . Indarto; Boedi Soesanto; Debby Rio Prasetyo (JURNAL AGROTEKNOLOGI, 2012)
This research aims to create Digital Elevation Model (DEM) manually, presenting information DEM Rawatamtu sub-watershed and evaluate DEM produced. A method of creating DEM using software ArcGIS 10 with input data obtained from digitazion map in a geocentric manner Indonesia (RBI) and survey the scorching tile with global positioning system (GPS). DEM that has been created having spatial resolution 10 meters with a height 3032,44 m.dpl maximum and minimum 33,82 m.dpl. Information from Rawatamtu subwatershed such as contour (showing the condition of the surface of the land), slope (showing the level of the steepness of the land), aspect (showing the direction of the slope), 3 dimensional display (visualize land forms in 3D), and line of sight (determine the state of a place can be seen from elsewhere). Based on the test results, DEM made manually with spatial resolution 10 meters, the level of error is relatively small and could describe characteristic of topography the watershed of more detailed.Keywords: DEM, watershed management, RBI’s maps, GPS